Draft Annual Plan 1983-84 Volume II Tamil Nadu - Planning Commission (Planning Commission, 1983)
According to the Quick Estimates for 1980-81, the Net State Domestic Product for Tamil Nadu at current prices aggregated to Rs 6,089.49 crores, as against Rs. 6,021.72 crores in 1979- 80, registering a marginal increase of IT per cent. In real terms (at 1970-71 prices), the Net State Domestic Product had decreased from Rs. 3,299.68 crores in 1979-80 to Rs. 3,031.62 crores in 1980-81, manifesting a decline of 8.1 per cent. The per capita income had shown a decrease in 1980-81 over the previous year both at current and at 1970-71 prices and in real terms, it had registered a decrease of about 9.5 per cent. This was mainly due to the substantial decline in the income from primary sector. the income from trade and unorganised manufacturing sectors had also shown a decline in 1980-81.
State Planning Commission Tamil Nadu